PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS COURSELAB PADA PRINSIP KERJA ENGINE BIDANG KEAHLIAN KENDARAAN RINGAN - Imam Wahyudi; Fitri Wijayanti (Jurnal Poli-Teknologi, 2019)
Development research focused on developing Courselab-based learning aids on the principle of Light Vehicle Engine Expertise which includes Student Books, Student Activity Sheets and Lesson Plans for grade XI SMK students. The model of development used in this research refers to the model of learning aids development of Dick & Carey which consists of three phases, namely (1) identification phase; at this stage the writing of goals and analysis of instructional learning is conducted, identifying initial behaviors and characteristics of the students, (2) development phase; at this stage the Courselab-based learning tools is developed by formulating the goals and the standard reference tests, as well as developing the strategies and the learning aids, (3) testing and evaluation phase. The developed Courselab-based learning aids has been validated by two experts with revision to obtain a result which is fit to use. The tests carried out in three stages, namely one-on-one testing, small group testing conducted at SMK Nasional Makassar to evaluate the practicality of the learning aids and limited testing conducted at SMK Darussalam Makassar to evaluate the practicality and the effectiveness of the learning aids. The research results show that the developed learning aids, after the validation, was declared valid. The learning aids is attributed practical as the students responded positively to the learning aids they used. The learning aids is considered effective as the students responded positively to the learning aids used. It has met the criteria of effectiveness, with the results: (1) student activities have met the predetermined tolerance limits, (2) the teacher activities have fulfilled the observed aspects, and (3) the student learning outcomes on the working engine principle materials have achieved completeness.